Preparation and characterization of transparent and foldable polysiloxane‐poly(methyl methacrylate) membrane with a high refractive index. Issue 36 (6th June 2015) - Xu, Jinku; Zhu, Weiyue; Zhang, Leilei; Zhang, Yongchun
ABSTRACT In this article, carbazole‐grafted methacrylic polysiloxane (MA‐CZ‐PDMS) macromonomer was synthesized and its structure was confirmed by proton nuclear magnetic resonance (1H NMR). The polysiloxane macromonomer can homogeneously copolymerize with methyl methacrylate (MMA) to prepare transparent and foldable carbazole‐grafted polysiloxane‐poly(methyl methacrylate) (PDMS‐PMMA) membranes with a high refractive index (RI). The membranes were characterized by light transmittance, RI value, and dynamic mechanical thermal analysis (DMTA). The results indicated that the carbazole‐grafted PDMS‐PMMA membranes had excellent light transmittance that decreased slightly with increasing carbazole‐grafted polysiloxane content. Incorporation of carbazole‐grafted polysiloxane in the materials improved its RI value; however decreased the glass transmission temperature (Tg) that can be adjusted to less than 30°C, enable the membrane foldable at room temperature. The data demonstrate that the carbazole‐grafted PDMS‐PMMA membranes have a potential application as high RI intraocular lens (IOL) suitable for implantation by minimally invasive surgery. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42491.